Anatomic anterior cruciate ligament reconstruction using an individualized approach - Carola F. van Eck; Freddie H. Fu (Elsevier, 2014)
Anterior cruciate ligament (ACL) reconstruction is one of the most commonly performed orthopaedic procedures. Recently, there has been a shift in interest towards reconstruction techniques that more closely restore the native anatomy of the ACL. This review paper discusses our approach to individualized anatomic ACL reconstruction, including the anatomy of the ACL, the physical exam, imaging modalities, the surgical technique for anatomic reconstruction including pre- and intraoperative considerations and our postoperative rehabilitation protocol.